2020
DOI: 10.1017/s136898002000422x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging adults’ intersecting experiences of food insecurity, unsafe neighbourhoods and discrimination during the coronavirus disease 2019 (COVID-19) outbreak

Abstract: Objective: Examine how food insecurity is related to emerging adults’ food behaviors and experiences of neighborhood safety and discrimination, and identify resources needed to support their health during the COVID-19 outbreak. Design: Rapid-response, online survey. Participants completed the 6-item U.S. Household Food Security Survey Module, a brief measure of food insufficiency, and measures of food behaviors, neighborhood safety, and discrimination. Open-ended questions were used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 40 publications
3
53
1
Order By: Relevance
“…In a study that included respondents from four Western countries, the average portions of fruits and vegetables consumed per day actually increased from before the pandemic to during the pandemic [47]. No studies to date have compared changes in fruit and vegetable intake between food-secure and food-insecure individuals, but one study of U.S. emerging adults found that food-insecure respondents had significantly lower home availability of fruits and vegetables compared with food-secure respondents [48].…”
Section: Discussionmentioning
confidence: 99%
“…In a study that included respondents from four Western countries, the average portions of fruits and vegetables consumed per day actually increased from before the pandemic to during the pandemic [47]. No studies to date have compared changes in fruit and vegetable intake between food-secure and food-insecure individuals, but one study of U.S. emerging adults found that food-insecure respondents had significantly lower home availability of fruits and vegetables compared with food-secure respondents [48].…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the C‐EAT (COVID‐19 Eating and Activity over Time) study were members of the EAT 2010–2018 cohort who were invited to complete a follow‐up, online survey during the COVID‐19 outbreak (Larson, Slaughter‐Acey, et al, 2021). The EAT 2010–2018 study is a population‐based investigation of weight‐related health behaviors and associated factors among young people who were attending secondary school in Minneapolis‐St.…”
Section: Methodsmentioning
confidence: 99%
“…All open‐ended comments were read by two independent raters (MS and RE), wherein raters identified responses that included a description of disordered eating, any changes to eating behaviors, or eating disorder symptoms. Given the broad scope of the qualitative survey question, additional research using these survey data has focused on qualitative responses pertaining to the impacts of the COVID‐19 pandemic on food availability, food preparation, and food insecurity (Larson, Slaughter‐Acey, et al, 2021). The deductive component of the qualitative analysis for the present study thus excluded responses pertaining to food access, preparation, and insecurity.…”
Section: Methodsmentioning
confidence: 99%
“…Participants in EAT 2010–2018 included a population-based sample of young people who attended middle school or high school in Minneapolis-St. Paul, Minnesota in 2009–2010, and were followed over time [ 18 , 19 , 20 ]. The C-EAT survey was designed to capture changes in eating and activity behaviors and markers of psychosocial well-being during COVID-19 [ 21 , 22 ]. Email, text message, and mailed invitations were sent during the months of April to October 2020 to the 1568 emerging adults who had completed the most recent follow-up survey in 2017–2018.…”
Section: Methodsmentioning
confidence: 99%